Hidden. Series 3 [videorecording (DVD)] - Newbery, Andy; Forster, Chris, 1971-; Lewis, Caryl, 1978-; Steffan Ros, Manon; Foley, Liam; Reese-Williams, Sian, 1981-; Davies, Sion Alun; Eifion, Siôn; Melluish, Justin; Roberts, Nia, 1972-; Rhys, Elen; Pugh, Victoria (Acorn, 2022)
When a body is found in a river, Cadi leads an investigation into the lives of two brothers. The brothers have secrets to hide, a harrowing history, but you can't outrun your past. --